IMPLEMENTASI MANAJEMEN PESERTA DIDIK DALAM MENINGKATKAN DAYA SAING DI MTs AL-AMIRIYYAH BLOKAGUNG BANYUWANGI - Aimah, Siti (Jurnal Manajemen Pendidikan Islam Darussalam, 2022)
In realizing quality students who are able to compete in various fields, for example in the field of knowledge, experience, abilities and skills that underlie the values ??and norms of life, one of the responsibilities of education, especially focused on preparing students to become subjects who increasingly play a role in displaying their superiority. , have a strong stand, creative, independent, and professional in their respective fields. This study aims to describe the management of students at MTs Al-Amiriyyah Blokagung Banyuwangi and to describe the competitiveness of students at MTs Al-Amiriyyah Blokagung Banyuwangi. The approach used in this research is a qualitative approach with a descriptive type of research. The methods used in data collection are observations related to the implementation of student management in increasing competitiveness, interviews with school principals and student waka, as well as documentation and archive data of activities from management at MTs Al-Amiriyyah Darussalam Blokagung. The researcher uses the Miles and Huberman model, namely reduction, presentation and conclusion drawing or data verification. The results of this study indicate that the implementation of student management at MTs AL-Amiriyyah blokagung banyuwangi has been well organized. where the management of students starting from: acceptance of students, grouping students, fostering student discipline and evaluation has been implemented by all units of MTs AL-Amiriyyah blokagung banyuwangi